Tactile internet and its applications in 5G era: A comprehensive review. (15th July 2019) - Gupta, Rajesh; Tanwar, Sudeep; Tyagi, Sudhanshu; Kumar, Neeraj
Summary: Over the last few years, communication latency has been a major hurdle for most of the applications deployed in different network domains. During this era, a number of communication protocols and standards were developed and used by the community. However, still, the problem of latency persists keeping in view of the quality of service (QoS) and quality of experience (QoE) for different applications. To mitigate the aforementioned issues, in this paper, we present an in‐depth survey of state‐of‐the art proposals having tactile internet as a backbone for delay mitigation using 5G networks for future ultra‐reliable low‐latency applications such as Healthcare 4.0, Industry 4.0, virtual reality and augmented reality, and smart education. From the existing proposals, it has been observed that tactile internet can provide interactions between virtual objects to give a feel of real environment with maximum latency of 1 millisecond. Also, this paper highlights the key differences between the tactile internet and Internet of Things in context with 5G revolution. Then open issues and challenges of tactile internet for smart applications are analyzed. Finally, a comparison of existing proposals with respect to various parameters is presented, which allows the end users to select one of the proposals in comparison with its merits over the others. Abstract : This paper presents a systematic review of tactile internet (TI) by exploring the latency and reliability issues for smart ultra‐reliable low latency applications. Then, introduce an in‐depth survey of the research challenges in creating smart applications with ultra‐low latency. Finally, this paper bridges the gap between the latency and other research challenges for ultra‐reliable low‐latency applications in 5G environment using TI.